一种用于实现全自动飞行校验的无人机系统和校验系统 (2024)
本发明涉及一种用于实现全自动飞行校验的无人机系统和校验系统。其中，所述无人机系统包括安装在无人机上的无人机飞行控制系统和无人机校验系统：其中，所述无人机飞行控制系统用于获取附加有参数化的校验科目指令的飞行计划，并且用于基于所述无人机对所述飞行计划的执行向所述无人机校验系统提供所述参数化的校验科目指令；以及，所述无人机校验系统用于基于所述提供的参数化的校验科目指令的控制，发送无人机校验数据，以供地面校验系统获取。本发明提出的方案可以实现全自动的无人机校验，可以大大提高飞行校验的效率，降低飞行校验成本，杜绝因地面校验人员误操作而引起校验取值无效的风险。 The invention relates to an unmanned aerial vehicle system for realizing full-automatic flight verification and a verification system. The unmanned aerial vehicle system comprises an unmanned aerial vehicle flight control system and an unmanned aerial vehicle verification system which are mounted on an unmanned aerial vehicle, wherein the unmanned aerial vehicle flight control system is used for obtaining a flight plan with a parameterized verification subject instruction, and is also used for providing the parameterized verification subject instruction for the unmanned aerial vehicle verification system based on execution of the unmanned aerial vehicle on the flight plan; and the unmanned aerial vehicle verification system is used for